Polysaccharide from Atractylodes macrocephala Koidz binding with zinc oxide nanoparticles: Characterization, immunological effect and mechanism - Bo, Ruonan; Liu, Xiaopan; Wang, Jing; Wei, Simin; Wu, Xinyue; Tao, Ya; Xu, Shuya; Liu, Mingjiang; Li, Jingui; Pang, Huan (Frontiers in Nutrition, 2022)
Atractylodes macrocephala Koidz (A. macrocephala) has been used both as a traditional medicine and functional food for hundreds of years in Asia. And it has a variety of biological activities, such as enhancing the ability of immunity and modulating effect on gastrointestinal motility. In this study, a water-soluble polysaccharide with molecular weight of 2.743 × 103 Da was isolated from the root of A. macrocephala. Polysaccharide from A. macrocephala (AMP) consisted of arabinose, galactose, glucose, xylose, mannose, ribose, galactose uronic acid, glucose uronic acid, with a percentage ratio of 21.86%, 12.28%, 34.19%, 0.43%, 0.92%, 0.85%, 28.79% and 0.67%, respectively. Zinc plays an important role in immune system. Therefore, we supposed that AMP binding with zinc oxide (ZnO) nanoparticles (AMP-ZnONPs) might be an effective immunostimulator. AMP-ZnONPs was prepared by Borch reduction, and its structural features were characterized by Scanning Electron Microscope (SEM), Transmission electron microscope (TEM), TEM-energy dispersive spectroscopy mapping (TEM-EDS mapping), Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectrometer (XPS), X-ray diffraction (XRD), particle size and zeta-potential distribution analysis. Then, its immunostimulatory activity and the underlying mechanism were evaluated using RAW264.7 cells. The results showed that AMP-ZnONPs remarkably promoted cell proliferation, enhanced phagocytosis, the release of nitric oxide (NO), cytokines (IL-6 and IL-1β) and the expression of co-stimulatory molecules (CD80, CD86 and MHCII). Moreover, AMP-ZnONPs could promote the expression of Toll-like receptor 4 (TLR4), Myeloid differentiation factor 88 (MyD88), TNF receptor associated factor 6 (TRAF6), phospho-IκBα (P-IκBα) and phospho-p65 (P-p65), and TLR4 inhibitor (TAK242) inhibited the expression of these proteins induced by AMP-ZnONPs. Therefore, AMP-ZnONPs activated macrophages by TLR4/MyD88/NF-κB signaling pathway, indicating that AMP-ZnONPs could act as a potential immunostimulator in medicine and functional food.